Genetic structure and isolation by distance in a landrace of Thai rice - Tonapha Pusadee (2018)
Rice is among the 3 most important crops worldwide. While much of the world's rice harvest is based on modern high-yield varieties, traditional varieties of rice grown by indigenous groups have great importance as a resource for future crop improvement. These local landraces represent an intermediate stage of domestication between a wild ancestor and modern varieties and they serve as reservoirs of genetic variation. Such genetic variation is influenced both by natural processes such as selection and drift, and by the agriculture practices of local farmers. How these processes interact to shape and change the population genetics of landrace rice is unknown. Here, we determine the population genetic structure of a single variety of landrace rice, Bue Chomee, cultivated by Karen people of Thailand. Microsatellite markers reveal high level of genetic variation despite predominant inbreeding in the crop. Bue Chomee rice shows slight but significant genetic differentiation among Karen villages. Moreover, genetically determined traits such as flowering time can vary significantly among villages. An unanticipated result was the overall pattern of genetic differentiation across villages which conforms to an isolation by distance model of differentiation. Isolation by distance is observed in natural plant species where the likelihood of gene flow is inversely related to distance. In Karen rice, gene flow is the result of farmers' seed sharing networks. Taken together, these data suggest that landrace rice is a dynamic genetic system that responds to evolutionary forces, both natural and those imposed by humans.